The Impact of Trans Sumatra Toll Road on the Retail Industry - Gunawan Kusumaatmaja; Mahjus Ekananda (EKO-REGIONAL, 2023)
The presence of a Trans Sumatra toll road in a region can promote national economic growth. The construction of a Trans Sumatra toll road also stimulates economic development in the region through which it passes. Applying the standard difference-in-difference (DiD) method, this study is to assess the impact of the Trans Sumatra toll road in 3494 villages from 2006 to 2019. It indicates that there was an average increase of 0.30 minimarkets in the villages that pass through the toll road compared to those that do not. Additionally, the effect of the increase in minimarkets is greater in villages located near the gate toll. The result indicates that there are an average of 0.90 more minimarkets in villages near the gate toll than in those that do not pass through the toll road. Even after controlling using variable control conflict and topography, this study's findings remain consistent. One of the strategic projects of the Indonesian government is the Trans Sumatra toll road, which is intended to boost the national economy by increasing regional development on the island of Sumatra.